2015
DOI: 10.1155/2015/917854
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Equine Herpesvirus Types 1 and 4 Infection in Healthy Horses in Isfahan Central and Shahrekord Southwest Regions, Iran

Abstract: This study was undertaken to investigate molecularly the occurrence of EHV-1 and EHV-4 infection among equine population in regions, Iran. Blood samples from 53 and 37 randomly selected horses settled in Isfahan and Shahrekord, Iran, respectively, were collected. Detection of EHV-1 and EHV-4 genes in the blood samples was done using polymerase chain reaction (PCR). Out of 53 and 37 samples from Isfahan and Shahrekord, 4 (18.18%) and 3 (8.10%) were positive for PCR of EHV-1, respectively. Nine (16.98%) and 6 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
(50 reference statements)
2
15
3
Order By: Relevance
“…While adult horses remain susceptible to infectious respiratory pathogens, the clinical expression of disease is often milder or remains subclinical especially in previously vaccinated horses. 13 This observation further highlights the diagnostic challenge equine practitioners face when presented with a horse displaying fever and other unspecific signs. The present study results showed that 7.2 per cent of horses with acute onset of fever tested qPCR-positive for ECoV in faeces, while only 1.4 per cent of them had detectable ECoV in nasal secretions by qPCR.…”
Section: Discussionmentioning
confidence: 88%
“…While adult horses remain susceptible to infectious respiratory pathogens, the clinical expression of disease is often milder or remains subclinical especially in previously vaccinated horses. 13 This observation further highlights the diagnostic challenge equine practitioners face when presented with a horse displaying fever and other unspecific signs. The present study results showed that 7.2 per cent of horses with acute onset of fever tested qPCR-positive for ECoV in faeces, while only 1.4 per cent of them had detectable ECoV in nasal secretions by qPCR.…”
Section: Discussionmentioning
confidence: 88%
“…8,9 While adult horses remain susceptible to infections with EHV-1, EHV-4, EIV, and ERBV, the clinical expression of disease is often milder or remains subclinical, especially in vaccinated horses. [10][11][12][13] Methicillin-resistant Staphylococcus aureus is a well-recognized nosocomial pathogen in human and veterinary medicine that has also been identified as a zoonotic pathogen. Although the majority of carriers of MRSA remain asymptomatic, nasal colonization can result in an increased likelihood of clinical infection in susceptible animals.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic of EHV is their ability to establish latency after a period of viraemia, when viruses persist subclinically in the host. In fact, latency in the trigeminal ganglia for EHV-1 and EHV-4 [ 5 ] and the lymphotropism of EHV-1, EHV-4, and EHV-2 were previously described [ 6 , 7 , 8 , 9 ]. Unfortunately, reactivation of latent virus, often as a result of a stress (transport, competition, immunosuppressive drugs, etc.…”
Section: Introductionmentioning
confidence: 99%